Surgical Management of Uterine Torsion in a Nulliparous Mongrel Bitch - Shivamurthy, Bhargav; Umapathi, Madhukumar (The Indian Journal of Animal Reproduction, 2025)
A two year old full term nulliparous mongrel bitch was presented with the history of impending parturition and presence  of greenish, blood tinged vulval discharge observed since twenty four hours. Upon physical examination, animal was dull  with evident signs of dehydration. Per vaginal examination revealed presence of foul-smelling greenish discharge and  absence of any foetal parts in the birth canal. Hematology revealed anemia with regenerative shift to left. Further ultrasonography revealed non-viable, multiple foetal skeletons with less echogenicity. Following, emergency caesarean section,  torsion was found in the uterine horn and four dead foetuses were removed and ovariohysterectomy was performed. Post  operative care was given with antibiotics and analgesics, eventually animal showed uneventful recovery.
Keywords: Bitch; Nulliparous; Ovariohysterectomy; Uterine torsion